PENGARUH INTENSITAS PENGGUNAAN GADGET TERHADAP HASIL BELAJAR MATEMATIKA SMP NEGERI 4 PAREPARE - Mita Permatasari (Tautologi: Journal of Mathematics Education, 2024)
This research aims to determine the positive influence of intensity of use on interest in learning mathematics in class VIII UPTD SMP Negeri 4 Parepare. This type of research is Ex-Post Facto. The population in this study were all students of class VIII UPTD SMP Negeri 4 Parepare which consisted of 5 classes. The sample chosen used the Cluster Random Sampling technique to obtain a sample of class VIII.5 which had a total of 35 students. Research data was obtained using a questionnaire sheet. Based on descriptive analysis, the average score obtained from the gadget use intensity questionnaire was 74.14, while the average score from the interest in learning mathematics questionnaire was 79.09. Inferential analysis using simple linear regression analysis obtained a probability value = 0.000. The significant probability value is smaller than α or p<α with α = 0.05 meaning that H0 is rejected and H1 is accepted. This shows that there is a positive influence of the intensity of gadget use on the interest in learning mathematics of class VIII UPTD students at SMP Negeri 4 Parepare.